Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Of course! Let's solve the expression [tex]\( 2^{-3} + (0.01)^{-\frac{1}{2}} - 27^{\frac{2}{3}} \)[/tex] step-by-step.
### Step 1: Evaluate [tex]\( 2^{-3} \)[/tex]
First, we calculate [tex]\( 2^{-3} \)[/tex]. The negative exponent indicates a reciprocal, so:
[tex]\[ 2^{-3} = \frac{1}{2^3} \][/tex]
Calculating [tex]\( 2^3 \)[/tex]:
[tex]\[ 2^3 = 8 \][/tex]
So:
[tex]\[ 2^{-3} = \frac{1}{8} = 0.125 \][/tex]
### Step 2: Evaluate [tex]\( (0.01)^{-\frac{1}{2}} \)[/tex]
Next, we calculate [tex]\( (0.01)^{-\frac{1}{2}} \)[/tex]. Again, the negative exponent indicates a reciprocal, so:
[tex]\[ (0.01)^{-\frac{1}{2}} = \frac{1}{(0.01)^{\frac{1}{2}}} \][/tex]
Finding the square root of [tex]\( 0.01 \)[/tex]:
[tex]\[ \sqrt{0.01} = 0.1 \][/tex]
Taking the reciprocal of [tex]\( 0.1 \)[/tex]:
[tex]\[ \frac{1}{0.1} = 10 \][/tex]
So:
[tex]\[ (0.01)^{-\frac{1}{2}} = 10 \][/tex]
### Step 3: Evaluate [tex]\( 27^{\frac{2}{3}} \)[/tex]
Next, we calculate [tex]\( 27^{\frac{2}{3}} \)[/tex]. This expression involves both a cube root and a square:
[tex]\[ 27^{\frac{2}{3}} = \left(27^{\frac{1}{3}}\right)^2 \][/tex]
Finding the cube root of [tex]\( 27 \)[/tex]:
[tex]\[ 27^{\frac{1}{3}} = 3 \][/tex]
Squaring the result:
[tex]\[ 3^2 = 9 \][/tex]
So:
[tex]\[ 27^{\frac{2}{3}} = 9 \][/tex]
### Step 4: Combine the results
Now, we combine the results from the previous steps:
[tex]\[ 2^{-3} + (0.01)^{-\frac{1}{2}} - 27^{\frac{2}{3}} = 0.125 + 10 - 9 \][/tex]
Simplifying the expression:
[tex]\[ 0.125 + 10 - 9 = 1.125 \][/tex]
### Step 5: Final result
Thus, the value of the expression [tex]\( 2^{-3} + (0.01)^{-\frac{1}{2}} - 27^{\frac{2}{3}} \)[/tex] is [tex]\( 1.125 \)[/tex]. Also, as individual terms, we have:
- [tex]\( 2^{-3} = 0.125 \)[/tex]
- [tex]\( (0.01)^{-\frac{1}{2}} = 10 \)[/tex]
- [tex]\( 27^{\frac{2}{3}} = 9 \)[/tex]
So the detailed result is:
[tex]\[ 2^{-3} = 0.125 \][/tex]
[tex]\[ (0.01)^{-\frac{1}{2}} = 10 \][/tex]
[tex]\[ 27^{\frac{2}{3}} = 9 \][/tex]
[tex]\[ \text{Result} = 1.125 \][/tex]
I hope this detailed solution helps you understand the steps involved in evaluating the expression!
### Step 1: Evaluate [tex]\( 2^{-3} \)[/tex]
First, we calculate [tex]\( 2^{-3} \)[/tex]. The negative exponent indicates a reciprocal, so:
[tex]\[ 2^{-3} = \frac{1}{2^3} \][/tex]
Calculating [tex]\( 2^3 \)[/tex]:
[tex]\[ 2^3 = 8 \][/tex]
So:
[tex]\[ 2^{-3} = \frac{1}{8} = 0.125 \][/tex]
### Step 2: Evaluate [tex]\( (0.01)^{-\frac{1}{2}} \)[/tex]
Next, we calculate [tex]\( (0.01)^{-\frac{1}{2}} \)[/tex]. Again, the negative exponent indicates a reciprocal, so:
[tex]\[ (0.01)^{-\frac{1}{2}} = \frac{1}{(0.01)^{\frac{1}{2}}} \][/tex]
Finding the square root of [tex]\( 0.01 \)[/tex]:
[tex]\[ \sqrt{0.01} = 0.1 \][/tex]
Taking the reciprocal of [tex]\( 0.1 \)[/tex]:
[tex]\[ \frac{1}{0.1} = 10 \][/tex]
So:
[tex]\[ (0.01)^{-\frac{1}{2}} = 10 \][/tex]
### Step 3: Evaluate [tex]\( 27^{\frac{2}{3}} \)[/tex]
Next, we calculate [tex]\( 27^{\frac{2}{3}} \)[/tex]. This expression involves both a cube root and a square:
[tex]\[ 27^{\frac{2}{3}} = \left(27^{\frac{1}{3}}\right)^2 \][/tex]
Finding the cube root of [tex]\( 27 \)[/tex]:
[tex]\[ 27^{\frac{1}{3}} = 3 \][/tex]
Squaring the result:
[tex]\[ 3^2 = 9 \][/tex]
So:
[tex]\[ 27^{\frac{2}{3}} = 9 \][/tex]
### Step 4: Combine the results
Now, we combine the results from the previous steps:
[tex]\[ 2^{-3} + (0.01)^{-\frac{1}{2}} - 27^{\frac{2}{3}} = 0.125 + 10 - 9 \][/tex]
Simplifying the expression:
[tex]\[ 0.125 + 10 - 9 = 1.125 \][/tex]
### Step 5: Final result
Thus, the value of the expression [tex]\( 2^{-3} + (0.01)^{-\frac{1}{2}} - 27^{\frac{2}{3}} \)[/tex] is [tex]\( 1.125 \)[/tex]. Also, as individual terms, we have:
- [tex]\( 2^{-3} = 0.125 \)[/tex]
- [tex]\( (0.01)^{-\frac{1}{2}} = 10 \)[/tex]
- [tex]\( 27^{\frac{2}{3}} = 9 \)[/tex]
So the detailed result is:
[tex]\[ 2^{-3} = 0.125 \][/tex]
[tex]\[ (0.01)^{-\frac{1}{2}} = 10 \][/tex]
[tex]\[ 27^{\frac{2}{3}} = 9 \][/tex]
[tex]\[ \text{Result} = 1.125 \][/tex]
I hope this detailed solution helps you understand the steps involved in evaluating the expression!
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.